Efficacy of a tetravalent dengue vaccine in healthy children aged 4–16 years: a randomised, placebo-controlled, phase 3 trial. Issue 10234 (2nd May 2020) - Biswal, Shibadas; Borja-Tabora, Charissa; Martinez Vargas, Luis; Velásquez, Hector; Theresa Alera, Maria; Sierra, Victor; Johana Rodriguez-Arenales, Edith; Yu, Delia; Wickramasinghe, V Pujitha; Duarte Moreira, Edson; Fernando, Asvini D; Gunasekera, Dulanie; et al.
Summary: Background: A substantial unmet need remains for safe and effective vaccines against dengue virus disease, particularly for individuals who are dengue-naive and those younger than 9 years. We aimed to assess the efficacy, safety, and immunogenicity of a live attenuated tetravalent dengue vaccine (TAK-003) in healthy children aged 4–16 years. Methods: We present data up to 18 months post-vaccination from an ongoing phase 3, randomised, double-blind trial of TAK-003 in endemic regions of Asia and Latin America (26 medical and research centres across Brazil, Colombia, Dominican Republic, Nicaragua, Panama, Philippines, Sri Lanka, and Thailand). Healthy children aged 4–16 years were randomly assigned 2:1 (stratified by age and region) to receive two doses of TAK-003 or two doses of placebo, 3 months apart. Investigators, participants and their parents or guardians, and sponsor representatives advising on trial conduct were masked to trial group assignments. Participants presenting with febrile illness were tested for virologically confirmed dengue (VCD) by serotype-specific RT-PCR. In timeframes beginning 30 days post-second dose, the primary endpoint (overall vaccine efficacy) was assessed in the first 11 months, and the secondary endpoints (efficacy by baseline serostatus, serotype, hospitalised dengue, and severe dengue) in the first 17 months. This study is registered with ClinicalTrials.gov, NCT02747927 . Findings: 20 099 participants were randomly assigned and vaccinated between Sept 7, 2016, and Aug 18, 2017; 19 021 (94·6%) were included in the per protocol analysis, and 20 071 (99·9%) in the safety set. The primary endpoint was achieved with an overall vaccine efficacy of 80·2% (95% CI 73·3 to 85·3; 61 cases of VCD in the TAK-003 group vs 149 cases of VCD in the placebo group). In the secondary endpoint assessment timeframe, an overall vaccine efficacy of 73·3% (95% CI 66·5 to 78·8) was observed. Analysis of secondary endpoints showed efficacies of 76·1% (95% CI 68·5 to 81·9) in individuals who were seropositive at baseline, 66·2% (49·1 to 77·5) in individuals who were seronegative at baseline, 90·4% (82·6 to 94·7) against hospitalised dengue, and 85·9% (31·9 to 97·1) against dengue haemorrhagic fever. Efficacy varied by individual serotypes (DENV 1, 69·8% [95% CI 54·8 to 79·9]; DENV 2, 95·1% [89·9 to 97·6]; DENV 3, 48·9% [27·2 to 64·1]; DENV 4, 51·0% [–69·4 to 85·8]). Cumulative rates of serious adverse events were similar in TAK-003 (4·0%) and placebo (4·8%) recipients, and were consistent with expected medical disorders in the study population. Infection was the most frequent reason leading to serious adverse events. 20 participants (<0·1% of the safety set) were withdrawn from the trial due to 21 adverse events by the end of part two; 14 of these participants received TAK-003 and six received placebo. Interpretation: TAK-003 was well tolerated and efficacious against symptomatic dengue in children regardless of serostatus before immunisation. Vaccine efficacy varied by serotype, warranting continued follow-up to assess longer-term vaccine performance. Funding: Takeda Vaccines.